Arbejdshypotesen om en menneskehed: Tidsskriftet Kritisk Revy mellem avantgarde og populærkultur - Jelsbak, Torben (Danske Studier, 2024)
The Danish architectural journal Kritisk Revy (1926-1929) occupies an important position in Danish cultural life and intellectual history of the 1920s. Edited by a group of young left-wing architects and intellectuals with the designer and critic Poul Henningsen as prime mover, the journal served as ideological platform and propaganda vehicle for the functionalist movement in Danish and Nordic architecture and design. In strong opposition to the conservative and neoclassicist tendencies prevailing in contemporary Danish architecture and housing policy, the journal agitated in favour of a ’rational city planning’, a ’social architecture’, and a ’reliable’ style in modern interior design that could reflect the social demands of modern democratic society. Kritisk Revy’s modern concept of architecture and interior design was developed in close contact with contemporary currents in European avant-garde art and architecture, such as Russian constructivism, the German Bauhaus-school and the Swiss architect and theorist Le Corbusier. Yet, Kritisk Revy’s field of interest was not limited to architecture and design, but also included a wide range of phenomena emanating from contemporary popular culture, such as the aesthetics of advertising and shop window design, jazz music, film and revue songs. Thus, nearly all areas of popular urban culture were embraced as part of the journal’s critical strategy of promoting a modern ’democratic’ or ’classless’ culture to replace traditional styles and genres of bourgeois culture. This article analyzes how Kritisk Revy’s ’cultural radical’ vision of modernity and cultural liberation was developed as a response to these two apparently opposing phenomena of cultural modernity, the artistic avant-gardes and capitalist popular culture.